Reliability and Construct Validity of the Short Form 36 Questionnaire for Conjunctival Tumor Patients in Indonesia - Indrakila, Senyum; Soewoto, Widyanti; Purnomo, Joko; Malindha, Erma; Prastawa, Reza Pahlevi (http://dharmais.co.id/, 2025)
Background: The Short Form 36 (SF-36) questionnaire was used to measure quality of life (QoL) in Indonesia for patients with various conditions. However, its validity and reliability, specifically for patients with conjunctival tumors, remain understudied. Given the limited research on health-related quality of life (HR-QoL) in this patient population, our research aims to fill this gap by validating the SF-36 specifically for conjunctival tumor patients. Method: This observational, cross-sectional study recruited patients with conjunctival tumors receiving treatment at the Department of Ophthalmology, Dr Moewardi Hospital, between May and July 2024, using consecutive sampling. Participants completed the SF-36 questionnaire in the Indonesian context. Validity was assessed through bivariate correlation analysis, examining the Pearson correlation value for each item's questionnaire with the total QoL score. Reliability was determined using scale reliability analysis, focusing on Cronbach's alpha coefficient. The data was processed using IBM SPSS version 26.Results: The Pearson correlation coefficients for the 36-item scores range from 0.345 to 0.797, indicating a moderate to significant correlation. The scale-level Cronbach's alpha for the comprehensive tool is 0.942, suggesting excellent internal consistency. The SF-36 demonstrated robust reliability across its eight domains, confirming its suitability for measuring QoL in this demographic. These findings confirm that the SF-36 questionnaire in the Indonesian context is highly reliable and has construct validity in conjunctival tumor patients.Conclusion: The SF-36 questionnaire in the Indonesian context exhibits a satisfactory reliability scale and construct validity in assessing the QoL of conjunctival tumor patients. Further research with a larger participant pool is recommended.